Comprehensive analysis of gene mutation and phenotype of tuberous sclerosis complex in China - Guo-qiang HUANG; Qiong-xiang ZHAI; Zhi-hong TANG; Chun WANG; Mu-qing ZHUO; Lin-gan WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
Objective To summarize the clinical features of tuberous sclerosis complex (TSC), the distribution and description of TSC gene, and to probe into the correlation of genotype with phenotype.  Methods According to the 1998 International Tuberous Sclerosis Complex Diagnostic Criteria, a total of 163 TSC patients with pathogenic mutation in TSC gene (3 cases were detected in our hospital, and the other 160 cases were collected from other institutions in China) were enrolled, and their gene detection results and clinical data were analyzed.  Results Among 163 cases, TSC1 mutation (31 cases) accounted for 19.02% [32.26% (10/31) in exon 15, 16.13% (5/31) in exon 21, 12.90% (4/31) in exon 18], and TSC2 mutation (132 cases) accounted for 80.98% [9.85% (13/132) in exon 37, 7.58% (10/132) in exon 40, 6.82%(9/132) in exon 33]. The proportion of base replacement in TSC1 was 41.94% (13/31), and 52.27% (69/132) in TSC2. Male patients exhibited significantly more subependymal nodules or calcifications than thefemale patients (χ2 = 8.016, P = 0.005). Sporadic patients exhibited significantly more cortical tubers than familial patients (χ2 = 6.273, P = 0.012). Patients with TSC2 mutations had significantly higher frequencies of hypomelanotic macules than patients with TSC1 mutations (χ2 = 6.756, P = 0.009). Patients with missense mutations were more likely to have facial angiofibromas compared with patients with other mutations (χ2 = 4.438, P = 0.035).  Conclusions Exon 15, 21 and 18 of TSC1 and exon 37, 40 and 33 of TSC2 accounted for higher percentage of mutations. Correlating genotypes with phenotypes should facilitate the individualized treatment and prognostic assessment of tuberous sclerosis complex.   DOI: 10.3969/j.issn.1672-6731.2015.04.013